Occupation, displacement, and violence in the West Bank: A retrospective analysis of data from 2014-2024. - Sarah Aly; Fatima Mossolem; Ayeh Khalil; Tushara Surapaneni; Abd Al-Rahman Traboulsi; Waleed Aldadah; Eleanor Reid; Shakoor Hajat (PLOS Global Public Health)
Israeli settlement expansion in the West Bank has intensified violence in the occupied Palestinian territories (oPt). This violence escalated after attacks by Hamas on Israel on 7 October 2023 and the subsequent military campaign in Gaza. This study examines the possible impacts of military and land occupation on displacement, injuries, and deaths in the West Bank. This cross-sectional observational study analyses casualties and displacement data in the West Bank and Israel from May 1, 2014, to June 30, 2024. Sources include the United Nations Office of Coordination of Humanitarian Affairs, Statista, and the Palestinian Central Bureau of Statistics. Death and injury rates per 100,000 person-years were calculated and compared across populations. Interrupted time-series analysis compared observed Palestinian deaths, injuries, and displacement to expected levels since October 2023. Chi-square analysis examined demolition patterns by West Bank area. GIS mapping methods visualized spatial variations in casualties and demolitions. Death and injury rates were substantially higher for Palestinians than Israelis: RR = 5.72 (95% CI 2.38, 13.75; p < 0.001) for deaths and RR = 16.47 (6.86, 39.56; p < 0.001) for injuries. Refugee camps had increased death rates: IRR = 7.91 (5.26, 11.89; p < 0.0001) compared to non-refugee camp populations. Since October 2023, West Bank deaths were 25% higher than expected: RR = 1.25 (1.15, 1.36; p < 0.0001) and displacement 17% higher: RR = 1.17 (1.12, 1.21; p < 0.0001). Nablus and Jenin recorded the highest fatalities. Jabal al-Mukkabir in East Jerusalem experienced the highest number of demolitions. Our study confirms a significant disparity in rates of conflict-related traumatic injuries and deaths between Palestinians and Israelis. The findings emphasize the need to limit military force against civilians, to hold the Israeli government accountable for demolitions and displacement, and to instigate protective measures in refugee communities. Policy efforts should prioritize conflict de-escalation, including reaching a sustainable political solution.